Studi Herbivori Rumput Laut Kappaphycus alvarezii (Doty) Doty oleh Ikan Baronang Siganus sp. pada Salinitas yang Berbeda - Framegari, Vera; Nirwani, Nirwani; Santosa, Gunawan Widi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Kappaphycus alvarezii is one of seaweed species widely cultivated for producing high economic value carrageenan as raw material for pharmaceutical, cosmetic, food, etc.. During the cultivation of this seaweed there are some constrains found that is by fish herbivory by rabbitfish (Siganus sp.). One of factors thought to affect fish herbivory rabbitfish on seaweed is the salinity. Therefore, there is a need to conduct observation on Siganus sp. Herbivory at different levels of salinity. This research used Completely Randomized Design (CRD) with 5 treatments with 3 replications, namely were the treatment A (salinity 28 ppt), treatment B (30 ppt salinity), treatment C (salinity 32 ppt), treatment D (34 ppt salinity), and treatment E (salinity 36 ppt). Data were analyzed statistically with one-way ANOVA using SPSS software. The results showed that the salinity treatment gave a very significant influence (P <0.01) of seaweed herbivory K. alvarezii by rabbitfish. The results of this study were showed that the total weight of seaweed eaten by rabbitfish during the maintenance period of 30 days were: treatment A = (149.19 g), treatment B = (191.17 g), treatment C = (298.12 g), treatment of D = (212.87 g) and treatment E = (89.15 g). Body weight of fish at the end of the study were: treatment A (33.93 ± 6.35 g), treatment B (34.51 ± 4.34 g), treatment C (49.79 ± 5.67 g), treatment D (33.44 ± 14.12 g) treatment E (32.44 ± 2.72 g).